THE IMPLEMENTATION OF STEM-INTEGRATED PROBLEM-BASED LEARNING TO IMPROVE STUDENTS’ MATHEMATICAL REASONING ABILITY - Senawati, Aulia; Noer, Sri Hastuti; Wijaya, Agung Putra (Universitas Bhinneka PGRI, 2025)
In the era of the industrial revolution 4.0, improving students' mathematical reasoning abilities is crucial. Student-centered, collaborative, contextual, and inclusive learning is key to facing this era. This study aimed to determine the improvement of the implementation of STEM-integrated problem-based learning on students' mathematical reasoning abilities. The population in this study were all VIII grade students of SMP Negeri 4 Bandar Lampung in the 2024/2025 academic year, which were distributed into 10 classes. The samples in this study were students of class VIII I as the experimental class and class VIII J as the control class, which were selected by a purposive random sampling technique. The research design used is the pretest-posttest control group design. Data on mathematical reasoning ability in quantitative data was collected through test instruments in the form of descriptions on the material of the system of linear equations of two variables. Data analysis used the Mann-Whitney U test. The test results indicate that the increase in mathematical reasoning abilities of students who participated in STEM-integrated problem-based learning was higher than that of students who took part in conventional learning. This study concludes that implementing learning with STEM-integrated, problem-based learning can improve students' mathematical reasoning abilities.